Summer book club - Mallery, Susan (Toronto, Ontario, Canada Canary Street Press, 2024)
In the small town of Los Lobos, California, three women join a local indie bookstore's summer book club--devoted entirely to romance novels--and become life-long friends as they navigate the messiness of motherhood, second chances and becoming the person you've always wanted to be.
Includes reader discussion guide and recipes.
113179
Keywords: Book clubs (Discussion groups) -- Fiction; Books and reading -- Fiction; Female friendship -- Fiction; Motherhood -- Fiction; Self-actualization (Psychology) in women -- Fiction; Man-woman relationships -- Fiction; Discussion groups -- Fiction; Friendship; California -- Fiction; Domestic fiction; Romance fiction; Novels; Romans